PENGARUH KOMPENSASI TERHADAP KINERJA KARYAWAN PT. BANK TABUNGAN NEGARA (PERSERO), TBK. KANTOR CABANG MANADO - Rumere, Lidya Octafia; Pio, Rianne Johnly; Tampi, Johny Revo Elia (JURNAL ADMINISTRASI BISNIS (JAB), 2016)
Abstract. This study aims to determine the effect of compensation to employee performance State Savings Bank, Tbk Manado. This research uses descriptive quantitative approach with tools simple correlation and regression analysis, to test the level of relationship and influence that occurs between the variable compensation with employee performance. Results indicate compensation linked to employee performance as evidenced by the coefficient of determination of 0.619. The performance of the employees affected by the compensation of 61.9%, and there are 38.1% is determined by other factors. We hope this research can be used as a reference in subsequent research by developing a variety of other variables related to human resources management.Keywords: Compensation, Employee Performance